Risks and harm on the Internet among the teenagers in Bangladesh - Taher, Taslim; Suhaimi, Mohd Adam (Institute of Electrical and Electronics Engineers Inc., 2016)
Teenagers nowadays cannot survive socially without internet. This justifies a study on the factors that help to reduce risk and harm on the internet for the teenagers. The World Wide Web (WWW) should be able to bring them together and provide easy access to information. This will result with a new generation of teenagers having quality lives and more knowledgeable. Unfortunately, this may not be the case. A severe increase in child abuse is happening through online in Bangladesh. In response to this problem, this research intends to investigate the reasons behind this and search for several options to overcome the risk and harm on the internet among the teenagers in Bangladesh. © 2016 IEEE.